תשובה:
# (x-3) / (x + 3) #
הסבר:
ראשית, היית גורם כל פולינומים ולקבל:
# 4x ^ 2-1 = (2x-1) (2x + 1) # #
# x ^ 2-6x + 9 = (x-3) ^ 2 #
בואו למצוא את אפסים של
1) # 2x ^ 2-5x-3 # ו 2) # 2x ^ 2 + 5x-3 # לפי הנוסחה הריבועית:
# x = (5 + -sqrt (25 + 24)) / 4 = (5 + -7) / 4 #
# x_1 = -1 / 2; x_2 = 3 #
לאחר מכן
1) # 2x ^ 2-5x-3 = 2 (x + 1/2) (x-3) = (2x + 1) (x-3) #
#x = (- 5 + -sqrt (25 + 24)) / 4 = (- 5 + -7) / 4 #
# x_1 = -3; x_2 = 1/2 #
לאחר מכן
2) # 2x ^ 2 + 5x-3 = 2 (x + 3) (x-1/2) = (x + 3) (2x-1) #
אז הביטוי הנתון הוא:
# (ביטול ((2x-1)) ביטול ((2x + 1))) / (ביטול ((2x 1)) ביטול ((x-3))) * ((x-3) ^ Cancel2) / (x + 3) לבטל ((2x-1))) #
# = (x-3) / (x + 3) #